The Logic of Coloniality and the Absence of Legal Liability for Transnational Companies for Human Rights Violations in the Production Chains: The Case of the Guarani and Kaiowá Indigenous People in Mato Grosso do Sul - Bragato, Fernanda Frizzo; da Silveira Filho, Alex Sandro (Revista de Estudos e Pesquisas sobre as Américas, 2021)
Drawing from the case of Guarani and Kaiowá indigenous people in Mato Grosso do Sul, this paper aims to analyze how the logic of coloniality relates to the transnational corporations’ lack of accountability for human rights violations occurred in their production chains. It is an explanatory research through through the historical and comparative methodologies, that adopts, as as research techniques, bibliographical and documentary analysis. The research results demonstrate that the logic of coloniality plays a central role in the lack of accountability of transnational corporations for human rights violations that occurred in the production chains. These results were verified to the extent that transnational companies, since their beginning, in the colonial period, have benefited from processes of dehumanization and subordination of individuals and groups (such as indigenous peoples) to expand and consolidate their political and economic power, persisting until now.